PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Ameilia Damayanti; Rianto Rianto (Program Studi Manajemen, 2020)
Current ratio, Debt to Equity Ratio, and Return on Equity are some of the many factors that are thought to have an influence on company value. Several studies have also used these factors as variables. Therefore, this study aims to test and reaffirm the results of previous studies with mixed conclusions. The sample of this study was 100 companies in manufacturing companies listed on the Indonesia Stock Exchange in the period 2018. The analysis technique used in this study is multiple regression analysis. The results showed that partially Current ratio, Debt to Equity Ratio had no significant effect on Company Value, while Profitability had a significant effect on Company Value. Simultaneously testing shows that current ratio, debt to equity ratio, and return on Equity have a significant effect on firm value.